Agricultural Extension Services and Climate Adaptive Capacity of Smallholder Farmers in Ebonyi State, Nigeria - Emeka Emmanuel Osuji; Michael Olatunji Olaolu; Ngozi Eucharia Okereke-Ejiogu; Peter Agu Onoh; Chidinma Adanna Peter-Onoh; Lilian Chinaenye Emma-Okafor; Ogueri Chukwuma; Chizoma Olivia Osuagwu; Bernadine Ngozi Aririguzo; Alagba Rosemond Adaohuru (Journal of Agricultural Extension)
Climate adaptive capacity of smallholder farmers through agricultural extension and climate information sources in Ebonyi State, Nigeria was evaluated.  Sample sizes of 428 smallholder farmers were selected through multi-stage sampling procedure. Data collected using questionnaire were analysed using percentage, and multivariate probit model. Source of agricultural extension service of smallholder farmers includes; farmer-to-farmer extension (99.6%), mobile phones (96.4%), radio (90.7%) and organized workshops/seminars (88.4%). Source of climate information service were farmer-to-farmer networks (94.4%), radio (90.6%), community meetings (85.4%) and mobile phones (81.6%). Planting of drought-tolerant crops (P<0.05), soil-water conservation (P<0.05), modifying planting dates (P<0.05), and implementing crop rotation systems (P<0.05) were significant adaptive strategies engaged by the smallholder farmers. Agricultural extension and climate information services enhanced adaptive capacity of smallholder farmers. Farmers were advised to engage proven adaptation measures to mitigate adverse effects of weather conditions.